Pengaruh dukungan pelayanan kesehatan terhadap pemberian asi eksklusif pada bayi sampai usia 4 bulan di Kota Pekanbaru - Zulfayeni Zulfayeni; Madarina Julia; Siti Helmyati (Jurnal Gizi Klinik Indonesia, 2005)
Background: The prevalence of exclusive breastfeeding until the age of 4 months is low. One of the many factors associated with it is healthcare supports on breastfeeding.Objective: The aim of this study was to assess the effect of healthcare supports for breastfeeding on the prevalence of exclusive breastfeeding until the age 4 months.Methods: This was a cohort study including 99 infants born at 10 birth clinics in Pekanbaru City during August-December 2003. Exposure was whether mother received supports for breastfeeding. Infants were followed monthly for 4 months to assess the duration they received exclusive breastfeeding.Results: Healthcare supports for breastfeeding were significantly associated with the duration of exclusive breastfeeding, i.e. RR (95%CI): 1.66 (1.08-2.54). Variables associated with longer duration of exclusive breastfeeding were availability of rooming in and early lactation. Early formula feeding did not support exclusive breastfeeding. Other variables associated with exclusive breastfeeding were husbands’ and other family members’ supports, maternal opinion on exclusive breastfeeding and maternal occupation.Conclusion: Healthcare supports on breastfeeding were important for promoting exclusive breastfeeding.